Individual adjustment and depression in a sample of oncological patients - Rodríguez, Beatriz; Bayón, Carmen; Orgaz, Pablo; Torres, Guadalupe; Mora, Fernando; Castelo, Beatriz (Psicooncología, 2008)
Psychological variables are the most consistent findings which associate depressión and oncologic illness. Objective: To analyze the relationship between personality dimensions and coping style in a sample of oncologic patients. Method: 40 patients with diagnosis of breast, colon or lung cancer, no metastasic, and a depressive disorder (DSM IV) were compared with a 39 patients with the same oncologic diagnosis but without depression. We used the MAC (Mental Adjustment Cancer Questionnaire) and the TCI-R (Temperament and Character Inventory of Clonninger). Results: Depressed patients showed coping styles characterized by anxious avoidance, fatalism and less fighting spirit. Depressed patients had personality dimensions with high scores in harm avoidance and low scores in recompense reward. Personality dimensions of persistence and auto-direction correlated with coping styles of hopelessness and fatalism in the depressed sample, while the same dimensions correlated with fighting spirit in the non depressed sample. The non depressed patients showed more fighting spirit when the tendency to harm avoidance was inferior. Conclusions: Our data supports the importance of personality and coping style evaluation and suggests the importance of the patient’s assumptive world as a possible mediator between personality, coping and depression.
Keywords: Coping style; Personality; Depression; Breast; lung; colon cancer